Relationship between Vitamin D status from childhood to early adulthood with body composition in young Australian adults - Zhu, K.; Oddy, W.H.; Holt, P.; Ping-Delfos, W.C.S.; McVeigh, Joanne; Straker, Leon; Mori, T.A.; Lye, S.; Pennell, C.; Walsh, J.P. (2019)
© 2019 Endocrine Society Context: Vitamin D plays a role in the differentiation and metabolism of skeletal muscle and, possibly, adipose tissue; however, the relationship between vitamin D status during growth and body composition in early adulthood is unclear. Objective: We examined associations between vitamin D status in childhood, adolescence, and early adulthood with body composition at age 20 years. Design, Setting, Participants: We studied 821 offspring (385 females) of the Western Australian Pregnancy Cohort Study who had $3 serum 25-hydroxyvitamin D [25(OH)D] at age 6, 14, 17, and 20 years and body composition assessed at age 20 using dual-energy x-ray absorptiometry. The participants were grouped into four vitamin D status trajectories: consistently lower, decreasing, increasing, and consistently higher. Results: The mean serum 25(OH)D at the study visits was 72.7 to 86.8 nmol/L. In males, serum 25(OH)D at 17 and 20 years was positively associated with lean body mass (LBM), and 25(OH)D at age 20 correlated negatively with fat body mass (FBM). Males with a consistently higher 25(OH)D trajectory had a 2.3- to 3.7-kg greater LBM and 4.1- to 6.0-kg lower FBM at 20 years compared with those with consistently lower or decreasing trajectories (P, 0.05 for all). In females, 25(OH)D at 14, 17, and 20 years was negatively associated with FBM. Females with increasing or consistently higher 25(OH)D trajectories had a 5.2- to 6.8-kg lower FBM at age 20 compared with those with a consistently lower trajectory (P, 0.05 for all). Conclusions: In the present predominantly white, relatively vitamin D-replete cohort, a higher vitamin D status trajectory from childhood to early adulthood was associated with a greater LBM in males and lower FBM in both sexes at age 20.